2009
DOI: 10.1210/me.2009-0048
|View full text |Cite
|
Sign up to set email alerts
|

ALU Repeats in Promoters Are Position-Dependent Co-Response Elements (coRE) that Enhance or Repress Transcription by Dimeric and Monomeric Progesterone Receptors

Abstract: We have conducted an in silico analysis of progesterone response elements (PRE) in progesterone receptor (PR) up-regulated promoters. Imperfect inverted repeats, direct repeats, and half-site PRE are widespread, not only in PR-regulated, but also in non-PR-regulated and random promoters. Few resemble the commonly used palindromic PRE with three nucleotide (nt) spacers. We speculated that PRE may be necessary but insufficient to control endogenous PR-dependent transcription. A search for PRE partners identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 68 publications
2
42
0
Order By: Relevance
“…Moreover, during these investigations, a possibility that the PR might also have a subset of PR-selective PREs became apparent. This was also suggested in a recent paper by Jacobsen et al (31). During the finalization of this manuscript, Jiang et al (40) described an androgen-responsive gene database.…”
Section: Evaluation Of Pspmsupporting
confidence: 57%
“…Moreover, during these investigations, a possibility that the PR might also have a subset of PR-selective PREs became apparent. This was also suggested in a recent paper by Jacobsen et al (31). During the finalization of this manuscript, Jiang et al (40) described an androgen-responsive gene database.…”
Section: Evaluation Of Pspmsupporting
confidence: 57%
“…Although this model has not been proven for polymorphic Alu elements, it is supported for evolutionarily older elements that are fixed in the genome, including Alu elements that act as tissue-specific enhancers (e.g., refs. 71,72). Fixed Alu can also provide alternatively used exons (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this, we found that the AR antagonist activity displayed by CpdA on a GRE-containing synthetic reporter in COS-1 cells was mimicked in BWTG3 cells for expressed AR-mediated regulation of endogenous TAT activity. It has been suggested that the flanking sequences around GREs may play an important role in receptor specificity (61) and that individual GREs retain specific "architectural signatures" that includes distinct GRbinding sites as well as binding motifs for other transcription factors (62). Thus by investigating only isolated transcription binding sites the role of these flanking sequences that may contribute to the composite elements (63) enriched for motives to GR as well as other transcription factors may be overlooked.…”
Section: Discussionmentioning
confidence: 99%